Association of sedentary behaviour patterns with dietary and lifestyle habits among public school teachers: a cross-sectional study - William Rodrigues Tebar; Diego Giulliano Destro Christofaro; Leandro Dragueta Delfino; Fernanda Caroline Gil; Jefferson Marinho De Souza; Marcelo Romanzini; Romulo Araujo Fernandes (BMJ Open)
Objectives To analyse the association of sedentary behaviour patterns with dietary and lifestyle habits among public school teachers.Design Cross-sectional study.Participants A sample of 245 teachers (186 women and 59 men) with mean age of 45.2 (±10.4) were randomly selected from public schools.Primary and secondary outcome measure Sedentary behaviour was assessed by hours spent watching television, computer and cellphone/tablet use and in sitting position. Sedentary breaks were reported in a Likert scale in domains of work and leisure time. Dietary habits were assessed by weekly consumption of fruits, vegetables, dairy products, fried foods, sweets, grains, cereals, white meat, soft drinks and snacks. Physical activity, smoking, alcohol consumption and socioeconomic status were assessed by using questionnaires.Results The prevalence of high sedentary behaviour, high sedentary breaks at work and at leisure was 57.9%, 67.7% and 70.2% in the sample, respectively. No relationship was observed of high sedentary behaviour with dietary and lifestyle habits in adjusted analysis. However, high sedentary breaks at work were associated with high consumption of dairy products (OR=1.93 (CI 1.07 to 3.51)) and cereals (OR=2.49 (CI 1.05 to 5.92)) and with being high physically active (OR=2.57 (CI 1.14 to 5.77)). High sedentary breaks at leisure time were associated with high consumption of fruits (OR=2.33 (CI 1.28 to 4.23)) and vegetables (OR=1.91 (CI 1.05 to 3.49)) and with be high physically active (OR=2.34 (CI 1.03 to 5.35)). High sedentary breaks were associated with better dietary habits even among teachers with high sedentary behaviour.Conclusion High sedentary breaks were associated with better dietary habits and with high levels of physical activity among public school teachers, even those with high sedentary behaviour.